Visions how science will revolutionize the 21st century - Kaku, Michio (New York Anchor Books, 1998)
Discusses the future of science and technology in the next one hundred years, drawing from interviews with scientists in a wide variety of disciplines to make predictions about developments in the fields of computer science, biogenetics, and quantum physics.
Part One. Visions -- Chapter 1. Choreographers of matter, life, and intelligence -- Part two. The computer revolution -- Chapter 2. The invisible computer -- Chapter 3. The intelligent planet -- Chapter 4. Machines that think -- Chapter 5. Beyond silicon: cyborgs and the ultimate Computer -- Chapter 6. Second thoughts: will humans become obsolete? -- Part three. The biomolecular revolution -- Chapter 7. Personal DNA codes -- Chapter 8. Conquering cancer - Fixing Our Genes -- Chapter 9. Molecular Medicine and the Mind/Body Link -- Chapter 10. To Live Forever? -- Chapter 11. Playing God: designer children and clones -- Chapter 12. Second thoughts: the Genetics of a Brave New World? -- Part four. The quantum revolution -- Chapter 13. The Quantum future -- Chapter 14. To reach for the stars -- Chapter 15. Toward a planetary civilization -- Chapter 16. Masters of space and time.
Includes bibliographical references (pages [356]-393) and index.
Keywords: Science -- Methodology; Science -- Forecasting; Technological forecasting; Quantum theory; Molecular biology; Computers and civilization; Twenty-first century -- Forecasts